Exponential convergence of a distributed divide-and-conquer algorithm for constrained convex optimization on networks - Emirov, Nazar; Song, Guohui; Sun, Qiyu (Expositiones mathematicae, 2025)
We propose a divide-and-conquer (DAC) algorithm for constrained convex optimization over networks, where the global objective is the sum of local objectives attached to individual agents. The algorithm is fully distributed: each iteration solves local subproblems around selected fusion centers and coordinates only with neighboring fusion centers. Under standard assumptions of smoothness, strong convexity, and locality on the objective function, together with polynomial growth conditions on the underlying graph, we establish exponential convergence of the DAC iterations and derive explicit bounds for both exact and inexact local solvers. Numerical experiments on three representative losses (L2 distance, quadratic, and entropy) confirm the theory and demonstrate scalability and effectiveness.